Racial and Ethnic Disparity in Oral Cancer Awareness and Examination: 2003 New York State BRFSS - Junhie Oh, DDS, MPH; Jayanth Kumar, DDS, MPH; Gustavo Cruz, DDS, MPH (Blackwell Synergy, 2008)
This study documents the level of oral cancer awareness and examination among New York State adults and evaluates the determinants of disparities in oral cancer detection.